PROFESSIOGRAM'S COMPONENTS FOR FUTURE TEACHER OF HEALTH STUDY - Vladimir V. Kolbanov (Russian State Vocational Pedagogical University, 2016)
The purpose of this article is a search of optimal decisions in the creation of unified system in training of health teacher and correction of necessary conditions for guarantee of functional competency of specialist in future in according to demands of federal standards for common and professional pedagogical education. Methods. The author's methodology based on long-term experience of training of teachers-valeologists in the system of postgraduate pedagogical education is the basis of this investigation. Method of investigation consists in filling-in the form and interview by 176 teachers in St.Petersburg on subject of pupils' healthy life style. Questionnaires and forms of interview contain two groups of questions. Indifferent questions for respondents are concerned to health essence and healthy life style and to factors determining a health. Questions on possible health-directed activity in schools are included there too. Questions directed on analysis of proper respondents proper qualities are included in the second questionnaire part. Complaints, anamnesis vitae and character of relation to professional duties are taken into account for additional evaluation of health, life style and functional state. Results of investigation are represented in five tables and in commentaries to them. Results have revealed positive teachers relation to discussed problem in general. Some teachers showed insufficient competence and indifferent relation to decision of discussed problem. However, there are teachers (about 68%) who may be trained for creating health service in schools. This teacher's quantity is enough for difficult problem decision. Scientific novelty of this investigation consists in methodological substantiation for unification of health-teachers training. Practical significance is dictated by availability of negative tendencies in a state of health of children and teenagers that has caused search of organizational and pedagogical problem resolutions of forming among pupils of requirement and skills for a healthy lifestyle.